Total carbon sequestration during an entire rotation period of oil palm in northern Borneo - Runesson, Josefin (2020)
Considerable amounts of carbon (C) has been lost from tropical forests as a result of continuous conversion of tropical forests into oil palm plantations. Therefore, a better understanding of the C budget and potential sequestration rate in oil palm plantations and how it compares to natural forests is needed. Which is crucial in order to provide a more reasonable C credit payment to limit the widespread land conversion of tropical forests to oil palm plantations. In this thesis, I quantified the amount of C in both above- and belowground pools, which included: aboveground oil palms, stumps, senesced fawns, fine litter, coarse woody debris, roots and soil over an entire rotation period of oil palm. I established 12 plots of similar conditions within a chrono sequence of oil palm, spanning from recently planted plantations <1 year old to a 22 year old plantation. Using this approach, I was able to calculate the carbon sequestration rate during an entire rotation period of oil palm as well as assess changes in different carbon pools. I estimated that 160-ton C ha-1 is lost when converting a secondary forest in Sabah Borneo to oil palm plantations. However, I found that rate of C sequestration (ton C ha-1 yr-1) in oil palm is considerably higher than C sequestration in primary and secondary tropical forests. Aboveground oil palm and soil C are the two major C pools in oil palm plantation, yet it is changes in aboveground oil palm during the rotation period that is responsible for the high C sequestration rate. I also estimated an economic profit of 37,333 USD during a rotation period based on data from the production of fresh fruit bodies. Comparing the profit to the difference in C sequestration between natural forests and oil palm plantation I calculated a C credit payment of 54-96 USD ton-1 CO2 that would be need to conserve carbon in tropical forests while at the same time provide the same economic revenue as oil palm production , which is considerably higher than the current price for C. Thus, if we want to limit the conversion of tropical forest to oil palm plantations the current C credit payment is not enough and addition payments for other ecosystem services (i..,e biodiversity and water quality) are needed.